Probability of Caries in Preschool Children when Detecting Str. Mutant - Jabbarova Zarnigor Bazarbayevna (Scientific Trends, 2024)
This paper presents the first results of the study on the diagnosis of early caries in Voronezh. The study included 30 preschool children who were examined in the morning and evening for the presence of Str. Caries in saliva. The use of modern reagents made it possible to quickly and reliably determine the quantitative content of carious streptococcus spp. This method can be used to identify risk factors for the development of caries early and for the prevention of caries in young children.
Keywords: Tooth decay, Str. Mutans, childhood, prevention.